Desenvolvimento de aplicativo móvel do serviço web PATROOL.com utilizando a tecnologia Appcelerator Titanium - Costa, Carlos Humberto Lopes (2012)
This work presents the development of a mobile application from a web service called “PATROOL.com” using a alternative technology to native programming in Java/Android. Technologies will be presented as Appcelerator Titanium, Geolocation and Google Maps API. The use of the platform Appcelerator Titanium will allow the application to develop once and available for various platforms such as: iOS, Android and BlackBerry.